Integrative Multi-Omics Analysis of Identified Ferroptosis-Marker RPL8 as a Candidate Oncogene Correlates with Poor Prognosis and Immune Infiltration in Liver Cancer - Fan, Shunli; Zhang, Sai; Kong, Dejun; Wang, Hao; Shi, Yuan; Wang, Zhenglu; Zheng, Hong (Combinatorial Chemistry & High Throughput Screening, 2023)
Background: Liver Hepatocellular Carcinoma (LIHC) is characterized by high malignancy, poor prognosis, and high recurrence rate worldwide. The role of ferroptosis in tumorigenesis and progression has been confirmed in previous studies. However, the multi-omics analysis in liver cancer of ferroptosis-markers RPL8 remains to be elucidated. Methods: In this analysis, the RPL8 mRNA expression was analyzed via the GEPIA, TIMER and UALCAN databases. In addition, we verified the mRNA expression of RPL8 by qRT-PCR experiment. The Kaplan-Meier plotter, UALCAN, TCGAportal and HPA databases were applied to evaluate RPL8 on prognosis and clinicopathological parameters. Moreover, we used TIMER and Kaplan-Meier plotter to analyze the correlation of RPL8 to immune cell infiltration and immune cell type markers to prognosis. In addition, networks and function enrichment between RPL8 coexpression genes were analyzed by GeneMANIA, cBioportal and Metascape databases. What’s more, we used FerrDb and GEPIA databases to analyze the correlation of 23 Ferroptosis-related genes with RPL8. Results: The mRNA expression of RPL8 was over-expressed in multiple cancers. In addition, transcription and translation levels of RPL8 in LIHC were significantly higher than normal tissues. Furthermore, higher expression of RPL8 was closely related to shorter OS in LIHC patients. The analysis of Kaplan-Meier plotter proved that RPL8 expression was related to stage, Sorafenib treatment, alcohol consumption and hepatitis virus. Moreover, the results showed that the methylation expression level of RPL8 was significantly associated with age, gender, grade, stage and TP53 mutation of LIHC. RPL8 and its co-expression genes were primarily involved in liver regeneration and immune system process. Immune infiltration analysis showed the RPL8 expression had positively correlated with immune cells and immune subtypes in LIHC. Furthermore, qRT-PCR experiment validated the expression difference of RPL8 in liver cancer. Conclusion: Our findings elucidated that ferroptosis-markers RPL8 may play an important role in prognosis, and significantly correlate with ferroptosis-related genes, it also revealed the potential of RPL8 as a novel therapeutic target for LIHC treatment and prognosis assessment.
Keywords: liver cancer